2021
DOI: 10.1002/jcb.29884
|View full text |Cite
|
Sign up to set email alerts
|

Alternative human eIF5A protein isoform plays a critical role in mitochondria

Abstract: The eukaryotic translation initiation factor 5A (eIF5A) is the only known protein containing the amino acid residue hypusine, essential for its activity. Hypusine residue is produced by a posttranslational modification involving deoxyhypusine synthetase and deoxyhypusine hydroxylase. Herein, we aimed to describe the role of the alternative human isoform A on mitochondrial processes. Isoform A depletion modulates oxidative metabolism in association with the downregulation of mitochondrial biogenesis-related gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 79 publications
1
5
1
Order By: Relevance
“…They used a specific siRNA to deplete only the longer eIF5A isoform without affecting the canonical one and observed the downregulation of the mRNA levels of several genes involved in mitochondria biogenesis, as well as a reduction in the levels of several OXPHOS proteins in HeLa cells. Contrary to the results of depleting canonical eIF5A, the depletion of the N-terminal extended eIF5A isoform led to an increase in oxygen consumption; however, it also produced more ROS and mitochondrial fragmentation, and increased the expression of the BAK pro-apoptotic protein, suggesting that the longer eIF5A isoform is necessary for mitochondrial dynamics and that its depletion results in mitochondrial dysfunction and apoptosis [146]. Except for the increase in oxygen consumption, other effects of depleting the longer eIF5A isoform recapitulate those found when depleting or inhibiting the canonical mammalian eIF5A isoform, raising the possibility that the strategies used, such as hypusination inhibition or RNA interference, against the canonical EIF5A1 sequence could also act on the longer eIF5A isoform.…”
Section: Eukaryotic Translation Initiation Factor 5a's Subcellular Lo...contrasting
confidence: 77%
See 3 more Smart Citations
“…They used a specific siRNA to deplete only the longer eIF5A isoform without affecting the canonical one and observed the downregulation of the mRNA levels of several genes involved in mitochondria biogenesis, as well as a reduction in the levels of several OXPHOS proteins in HeLa cells. Contrary to the results of depleting canonical eIF5A, the depletion of the N-terminal extended eIF5A isoform led to an increase in oxygen consumption; however, it also produced more ROS and mitochondrial fragmentation, and increased the expression of the BAK pro-apoptotic protein, suggesting that the longer eIF5A isoform is necessary for mitochondrial dynamics and that its depletion results in mitochondrial dysfunction and apoptosis [146]. Except for the increase in oxygen consumption, other effects of depleting the longer eIF5A isoform recapitulate those found when depleting or inhibiting the canonical mammalian eIF5A isoform, raising the possibility that the strategies used, such as hypusination inhibition or RNA interference, against the canonical EIF5A1 sequence could also act on the longer eIF5A isoform.…”
Section: Eukaryotic Translation Initiation Factor 5a's Subcellular Lo...contrasting
confidence: 77%
“…The extended N-terminal sequence contains a putative mitochondrial localization signal and, indeed, when the longer eIF5A isoform was overexpressed in human HeLa cells, it was co-purified with the mitochondria [145]. More recently, the same group investigated the role of the longer eIF5A isoform on mitochondrial function [146]. They used a specific siRNA to deplete only the longer eIF5A isoform without affecting the canonical one and observed the downregulation of the mRNA levels of several genes involved in mitochondria biogenesis, as well as a reduction in the levels of several OXPHOS proteins in HeLa cells.…”
Section: Eukaryotic Translation Initiation Factor 5a's Subcellular Lo...mentioning
confidence: 99%
See 2 more Smart Citations
“…The isoform A has an extended N‐terminal sequence containing 30 amino acids not present in the isoform B and drives its association with mitochondria [ 17 ]. Thus, the question is whether this interaction has some functional relevance, even if the isoform A is quantitatively lower compared to the isoform B. Pereira et al [ 89 ] reported that depletion of the isoform A, using siRNA specific to the EIF5A1 variant A (siVA), modulated oxidative metabolism in association with down-regulation of mitochondrial biogenesis‐related genes. They observed a decrease in the protein content of complexes II and V and an increase in complex III, in parallel with a metabolic shift from oxidative to glycolytic metabolism.…”
Section: Apoptosis and Mitochondriamentioning
confidence: 99%